Electrical Transfer of Molecule Information into Water, Its Storage, and Bioeffects on Plants and Bacteria - Jerman, Igor; Ru i, Romana; Krašovec, Rok; Škarja, Metod; Mogilnicki, Lea (Electromagnetic biology and medicine, 2005)
The controversial phenomenon of the so-called water memory recently has been gaining in scientific credibility, either through direct empirical findings or theoretical considerations. The related researches mostly tackle the phenomenon subject to the homeopathic procedure, that is, a sequence of dilutions and shakings. Most likely this phenomenon is mediated via phonons originating from shaking. According to both our and other' experiments, we assumed that besides phonons polarization waves originating from a strong pulsed electric field also would transmit molecule information into water. The hypothesis was tested experimentally on various biological systems-here we describe the tests on bacteria and plants. The results were very positive and encouraging: Both organisms reacted to an information imprint of a chosen substance. Since both groups of experiments were performed in different places and under different researchers there is a very strong indication that the phenomenon is real, which put forth new questions and research possibilities.